(untitled) (diségno, 2018)
The research examines a large di sotto in su canvas entitled Apotheosis of Venice, realized between 1579 and 1582 by Paolo Veronese for the ceiling of the Hall of the Great Council of the Ducal Palace in Venice. The telero, surveyed with the tools of digital photogrammetry, was compared with a preliminary model of smaller dimensions. From the geometric comparison of the two works, in reference to the location of the main vanishing point and its relation to the real enclosure, it was found that the author planned the perspective apparatus of the painting by assigning a precise position to the observer. Applying the operations of perspective restitution to the architectural apparatus of the canvas and reconstructing the plans and the heights of the painted scene, we have come to a stereometric modeling that has allowed a greater understanding of the work. Further considerations which emerged from the analysis of the preparatory drawing have also made it possible to hypothesize the use of a direct system of perspective construction by the Caliari workshop.